2016
DOI: 10.1001/jamaoncol.2016.2214
|View full text |Cite
|
Sign up to set email alerts
|

Genomics- and Transcriptomics-Based Patient Selection for Cancer Treatment With Immune Checkpoint Inhibitors

Abstract: Genomics provides powerful tools for the identification of biomarkers for response to immune checkpoint blockade, given their potential to analyze multiple parameters simultaneously in an unbiased manner. This offers the opportunity for genomics- and transcriptomics-based selection of patients for rationally designed therapy with immune checkpoint inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 54 publications
0
51
0
Order By: Relevance
“…It is currently a matter of debate which biomarkers may best predict response to checkpoint inhibitors. Mutational burden, composition and activity of a preexisting immune infiltrate and mechanisms of tumor escape from immune surveillance are considered important components associated with the probability of response (Dijkstra et al 2016).…”
Section: Immunotherapy In Neuroendocrine Tumorsmentioning
confidence: 99%
“…It is currently a matter of debate which biomarkers may best predict response to checkpoint inhibitors. Mutational burden, composition and activity of a preexisting immune infiltrate and mechanisms of tumor escape from immune surveillance are considered important components associated with the probability of response (Dijkstra et al 2016).…”
Section: Immunotherapy In Neuroendocrine Tumorsmentioning
confidence: 99%
“…Despite these encouraging results, a large fraction of patients does not respond to current immunotherapies. Treatment failure may be explained at many different levels that include a low number of immunogenic antigens, defective antigen presentation, and/or the expression of alternative immune checkpoint molecules (Blank et al, 2016; Dijkstra et al, 2016; Pitt et al, 2017; Sharma et al, 2017). Given the large variety in mechanisms of immune evasion by cancers, it is presently challenging to predict whether an individual patient will be sensitive to immunotherapy, what mechanism is likely to underlie resistance and what alternative treatment could potentially overcome such resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Programmed death ligand 1 (PD‐L1) is a transmembrane protein expressed on immune cells (IC) and tumour cells (TC), whereas programmed cell death (PD)‐1 is expressed on IC and its expression can be induced following T cell activation. Upon binding to the receptor PD‐1 in IC, the overexpressed PD‐L1 in TC leads to functional inactivation of T cells and down‐regulation of T cell antitumoral activity, resulting in immune evasion . In recent years, PD‐L1 and PD‐1 have emerged as a key check‐point that can be manipulated with inhibitory monoclonal antibodies in various cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding to the receptor PD-1 in IC, the overexpressed PD-L1 in TC leads to functional inactivation of T cells and down-regulation of T cell antitumoral activity, resulting in immune evasion. [1][2][3][4][5] In recent years, PD-L1 and PD-1 have emerged as a key check-point that can be manipulated with inhibitory monoclonal antibodies in various cancer types. Multiple prospective randomised clinical trials have shown promising results of PD-1/PD-L1 immune check-point inhibitors in a variety of cancer types, including a subset of patients with urothelial carcinoma (UC), [5][6][7][8] breast carcinoma (BC) 9,10 and head and neck squamous cell carcinoma (HSCC), [11][12][13][14] leading to the Food and Drug Administration (FDA) approval of several anti-PD-1/ PD-L1 agents.…”
Section: Introductionmentioning
confidence: 99%